KOMUNIKASI DATA VIA KOMPUTER - Warno, Warno (potensio, 2008)
Computers became indispensable in the development ofinformation and communication, computer media and advancesin communications technology has an effect on thedevelopment of data processing. The majority of computerusers is available at companies or offices, and a large companyoften have branch offices. With so required data maybe transferred from one branch to another branch with telecommunicationsequipment, which encourage the functioningof a computer to generate information that truly reliableand fixed time. In broad outline of a circulation system consistingof data processing from data collection, processing,and distribution. For the data using a computer, data transmissionusing an electronic transmission system, usuallyreferred to as data communication. In response to this, theneed for skilled workers and who have knowledge of datacommunications is required. This paper will describe the technicalworkings of how data communications using a computer.Components required for data communication andother forms of data communication itselfKey word: Communication, computer